2005
DOI: 10.1165/rcmb.2005-0005oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyclosporin A on Airway Cell Proinflammatory Signaling and Pneumonia

Abstract: (Received in original form January 5, 2005 and in final form April 11, 2005) This work was supported by an NIH grant (HL60293) to A.P. and by a Cystic Fibrosis Foundation Fellowship to V.W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
(38 reference statements)
1
18
1
Order By: Relevance
“…Our data demonstrate that calcineurin plays an important role in the mediation of TLR2-stimulated CCL5 production by M. bovis BCG-infected cells, since we found that TLR2-mediated induction of CCL5 was greatly reduced by the calcineurin inhibitor FK-506. This finding is in excellent agreement with previous studies showing that another calcineurin inhibitor, cyclosporine, achieved significant inhibition of TLR2-mediated induction of CXCL8 secretion (38). It is interesting to consider the potential effects of calcineurin on several different transcription factors that could be involved in CCL5 production.…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrate that calcineurin plays an important role in the mediation of TLR2-stimulated CCL5 production by M. bovis BCG-infected cells, since we found that TLR2-mediated induction of CCL5 was greatly reduced by the calcineurin inhibitor FK-506. This finding is in excellent agreement with previous studies showing that another calcineurin inhibitor, cyclosporine, achieved significant inhibition of TLR2-mediated induction of CXCL8 secretion (38). It is interesting to consider the potential effects of calcineurin on several different transcription factors that could be involved in CCL5 production.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we chose to examine the role of two other transcription factor families, CREB and C/EBP, in basal and calcineurin-activated IL-6 promoter activity for three reasons: 1) binding sites for these transcription factors have been previously identified in the IL-6 promoter region, and they are known to regulate IL-6 promoter activity in other cell types (13,18,37,54); 2) their activity can be altered by calcineurin signaling (7,28,31,56,64); 3) repression of MEF-2 activity by MITR cotransfection was unable to eliminate all of the calcineurin induction of the IL-6 promoter, suggesting that other pathways contribute to this response. We found that, as has been shown previously for other cell types (13,18,37,54), mutation of the CREB or C/EBP binding sites alone significantly attenuated basal IL-6 promoter activity, and mutation of both together decreased basal IL-6 promoter activity to ϳ10% of wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because CREB and the C/EBP family of transcription factors can also be activated by calcineurin signaling (7,31,57,64) and are known to regulate IL-6 transcription in other cell types (13, 18, 37, 54), we evaluated the effects of these transcription factors on basal and calcineurin-stimulated IL-6 promoter activity. Cotransfection with either a constitutively active CREB or a wild-type C/EBP-␦ construct was sufficient to significantly increase IL-6 promoter activity in C 2 C 12 myotubes (Fig.…”
Section: Exercise Parameters As Shown Inmentioning
confidence: 99%
“…Patients with immune suppression therapy have been shown to have elevated level in the serum IL-6 (Tilg et al, 1992). The pro-inflammatory effect of Cys (Waters et al, 2005) and its effect on expression of IL-2 drives IL-6 secretion (Musso et al, 1992) was documented. In contrast to the current result long term treatment (more than one year) with cyclosporine caused significant decrease in serum IL-6 (Hanudle et al, 2016) and CRP (Madhok et al, 1991).…”
Section: Effect Of S Officinalis On Igg Concentration In Acrylamide mentioning
confidence: 99%